Studi Kinerja Wastewater Treatment Plant (WWTP) pada PLTGU Menggunakan Metode Deskriptif - Mutiara Saniyyah Rochmasia; Yayok Suryo Purnomo; Berta Ryza Harsativa; Arleen Maranatha Siahaan (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2025)
Using a descriptive method with a triangulation approach including observation, document analysis, and interviews this study ensures data reliability. Daily monitoring is conducted on wastewater flow and pH levels, while monthly laboratory analysis covers eight key parameters: Total Suspended Solids (TSS), iron (Fe), copper (Cu), zinc (Zn), total chromium (Cr), phosphate (PO³), oil and grease, and pH to evaluate the perfomance of the treatment system. The treatment process begins with the inflow of 960 m³ of wastewater per day into the storage pond, where aeration is applied to ensure homogenization before being transferred to the neutralization unit. pH adjustment is carried out by adding NaOH or HCl before the wastewater undergoes coagulation and flocculation stages. The study’s findings indicate that the WWTP meets the environmental quality standards established in accordance with the Decree of the Head of the Investment Coordinating Board of the Republic of Indonesia (2020), Number SK.214/1/KLHK/2020 concerning the Permit for Wastewater Disposal into the Sea on Behalf of PT Pembangkit Jawa Bali Unit Pembangkitan Gresik. This study emphasizes the importance of systematic monitoring and treatment in wastewater management.